Confirmatory Factor Analysis of the Malay Version of the Malaysia Medication Adherence Assessment Tool (MyMAAT) Among Patients with Chronic Medications - Ong GT; Abdullah S; Bachok NB (Patient Preference and Adherence)
Gaik Tian Ong, Sarimah Abdullah, Norsa’adah binti Bachok Biostatistics and Research Methodology Unit, School of Medical Sciences, Universiti Sains Malaysia, Kubang Kerian, Kelantan, MalaysiaCorrespondence: Sarimah Abdullah, Biostatistics and Research Methodology Unit, Universiti Sains Malaysia, Jalan Raja Perempuan Zainab 2, Kubang Kerian, Kota Bharu, Kelantan, 16150, Malaysia, Tel +60199569759, Email sarimah@usm.myPurpose: The bilingual Malaysia Medication Adherence Assessment Tool (MyMAAT) was developed using the Exploratory Factor Analysis (EFA) and the current study intended to confirm the measurement model, dimensionality and ensure the factor structure by the Confirmatory Factor Analysis (CFA). The objective of this study was to validate the Malay version of the MyMAAT in measuring medication adherence among participants with chronic medications.Patients and Methods: A cross-sectional study was conducted using a self-report questionnaire at five health clinics and a hospital in Kuala Lumpur and Putrajaya region between May to November 2023. The participants were selected using quota sampling and written informed consent was obtained from each participant prior to data collection. There are two constructs in the MyMAAT, namely the Specific Medication-Taking Behaviour (Factor 1) and the Social-Cognitive Theory of Self-Efficacy and Social Support (Factor 2).Results: Four hundred and seventy participants participated in the CFA study. The final model for the Malay version of the MyMAAT retained the two constructs and 12 items with good fit: CFI = 0.978, TLI = 0.973, RMSEA = 0.036 (90% CI 0.001,0.067) and with good composite reliability CR 0.790 for Factor 1 and 0.787 for Factor 2. The factor loadings ranged from 0.413 to 0.832 with p-value < 0.001. The AVE for Factor 1 was 0.664 and for Factor 2 was 0.491. There was a strong correlation (ρ = 0.507, p < 0.001) between the Malay version of the MyMAAT and the Malay version of the MMAS-8 by adherence category from the data of 191 participants. Twenty-six participants completed the test–retest after five to ten days from the first administration. The Malay version of the MyMAAT showed moderate to excellent with ICC 0.932 (95% CI: 0.661,0.986) for Factor 1 and poor to excellent for with ICC 0.956 (95% CI:0.325,0.997) for Factor 2 by using the Two-Way Mixed Model and Consistency type.Conclusion: It is concluded that the Malay version of the MyMAAT is valid and reliable in measuring medication adherence among patients with chronic medications.Keywords: validation, questionnaire, medication-taking behaviour, social-cognitive theory, self-efficacy, social support